The Incidence of Payroll Taxes - Underhill, H. Fabian (Quarterly Journal of Economics, 1942)
Journal Article The Incidence of Payroll Taxes Get access H. Fabian Underbill H. Fabian Underbill University of Illinois Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 57, Issue 1, November 1942, Pages 160–162, https://doi.org/10.2307/1881819 Published: 01 November 1942